Merger and Acquisitions Integration, Implementation as Innovative Approach Toward Sustainable Competitive Advantage: A Case Analysis From Chinese Sports Brands - Chiu, Wen-Hong; Shih, Yuan-Shen; Chu, Li-Sheng; Chen, Shieh-Liang (Frontiers in Psychology, 2022)
Brand M&A has long been an extremely common strategy for expanding the scale of an organization and entering new business areas, but various signs show that many brand mergers and acquisitions (M&As) do not add value. In fact, they often lose money and end in failure. This research explores the value, scarcity, and non-replicability of resources in corporate M&A, as well as organizational resource management, innovation resource management, and implementation of the combination of resource utilization and brand strategy incorporate M&As. Taking 03 of China’s sporting shoe industry cases, this study uses the literature to collect, analyze, and organize the conversations of high-level managers to compare and integrate the motivations of corporate M&As to conduct confirmatory analysis. Through the collection of case studies and cross-border M&A-related secondary data from 2014 to 2021 and supplemented by senior executives’ conversations, in total 1,836 articles were collected as analysis units. The research results show that the main corporate strategic motives of Chinese companies' cross-border M&As have four key elements: accelerated expansion, integration of resources, brand integration rapid entry into the international market, and obstacles to the construction of new entrants. The research results also show that the integration of resources and brand execution strategies after M&As correlates to their success or failure. The purpose of the research was first to discuss brand M&As and corporate strategies. Secondly, it discusses the issue of the use of resources by the acquired party. Third, it analyzes the effectiveness of brand strategy integration and implementation. Finally, it provides a strategic reference for brand M&As in the industry.